2019
DOI: 10.3389/fmed.2019.00046
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Tissue: Turning the Page to Precision Medicine in Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease targeting the joints. Current treatment strategies are based on clinical, biological and radiological features, yet still fail to reach the goal of early low disease activity in a significant number of cases. Hence, there is a need for refining current treatment algorithms, using accurate markers of response to therapy. Because RA induces histological and molecular alterations in the synovium even before apparition of clinical symptoms, synov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
1
17
0
1
Order By: Relevance
“…Several studies were performed in order to understand the mechanisms driving heterogeneity in histological, cellular and molecular changes in rheumatoid synovitis and investigate whether synovial cellular and molecular patterns can be linked to clinical outcomes (5)(6)(7)(8)(9)(10)(11). Thus, clinical variables such as disease activity, disease duration, ACPA status or response to specific therapies were associated with variations in cellular populations and molecular profiles in RA synovial biopsies (12). We and others reported that disease activity correlates with the expression of T cell-and myeloid-related transcripts in RA synovitis (2,6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were performed in order to understand the mechanisms driving heterogeneity in histological, cellular and molecular changes in rheumatoid synovitis and investigate whether synovial cellular and molecular patterns can be linked to clinical outcomes (5)(6)(7)(8)(9)(10)(11). Thus, clinical variables such as disease activity, disease duration, ACPA status or response to specific therapies were associated with variations in cellular populations and molecular profiles in RA synovial biopsies (12). We and others reported that disease activity correlates with the expression of T cell-and myeloid-related transcripts in RA synovitis (2,6,11).…”
Section: Introductionmentioning
confidence: 99%
“…Many targeted therapeutic options are available in RA, but therapy selection is a challenge because these options have similar treatment outcomes. Precision medicine tools are greatly needed to identify which patients have the appropriate disease biology for each targeted therapy [ 1 – 3 , 7 , 8 ]. The blood-based MSRC analyzes gene expression data along with common clinical features to accurately identify targeted-therapy naïve and TNFi-exposed patients who were unlikely to have an adequate response to TNFi therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because clinical guidelines do not recommend one treatment over another [ 1 , 4 ], therapy selection is often driven by administrative decisions and TNFi therapies remain the prevailing treatment in nearly 90% of patients with RA [ 5 , 6 ]. Matching each patient with the right targeted therapy to reach treat-to-target goals of low disease activity (LDA) or remission is an unmet medical need in RA [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A synovial biopsy is often performed for research purposes for example in RA patients; synovium histological and molecular alterations are considered a target for identifying new biomarkers to help rheumatologists tailor their clinical and therapeutic decision according to patient characteristics (7). Recently, a multicenter randomized control trial highlighted the possibility to integrate molecular pathology into clinical practice to improve treatment allocation of specific targeted therapies (8).…”
Section: When Should the Synovial Biopsy Be Done?mentioning
confidence: 99%